Financial Ratio Analysis as a Performance Indicator - ikhsanabdulsyukur; Siti Mariani Basanang (Faculty of Business and Economics , Universitas Yapis Papua, 2025)
Research this aiming For know performance finance at CV. Mutiara Hollow Sentani company for the period 2021-2023 with use analysis ratio finance. The type of research used in study is quantitative data analysis. Data collection using secondary data obtained​ from report finances that have been processed accounting division finance. Population and sample taken based on criteria certain or Purposive Sampling. Research results can concluded that If seen from side ratio activity is good.